2015
DOI: 10.1002/pi.4942
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of ion‐imprinted resin based on modified melamine–thiourea for selective removal of Hg(II)

Abstract: A novel Hg(II) ion‐imprinted resin based on thiourea‐modified melamine was manufactured for selective elimination of Hg2+ from aqueous solutions. The polymerizable thiourea–melamine ligand together with its Hg(II) complex were extensively investigated using elemental analysis, Fourier transform infrared (FTIR) and 1H NMR spectroscopies. The Hg(II) complex was used in a condensation polymerization in the presence of formaldehyde crosslinker and then the Hg(II) ions were leached out from the crosslinked polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The literature reported that coordination number for Hg (II) is four . In our investigation, the functional group content of HS‐PPS and AP‐PPS were about 2.2 and 1.71 mmol g −1 , and their adsorption capacities for Hg (II) were up to 210.65 (1.050 mmol g −1 ) and 169.06 mg g −1 (0.843 mmol.g −1 ) at 298 K, respectively.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…The literature reported that coordination number for Hg (II) is four . In our investigation, the functional group content of HS‐PPS and AP‐PPS were about 2.2 and 1.71 mmol g −1 , and their adsorption capacities for Hg (II) were up to 210.65 (1.050 mmol g −1 ) and 169.06 mg g −1 (0.843 mmol.g −1 ) at 298 K, respectively.…”
Section: Resultsmentioning
confidence: 50%
“…The literature reported that coordination number for Hg (II) is four. [51][52][53][54][55][56] In our investigation, the functional group content of HS-PPS and AP-PPS were about 2.2 and 1.71 mmol g À1 , and their adsorption capacities for Hg (II) were up to 210.65 (1.050 mmol g À1 ) and 169.06 mg g À1 (0.843 mmol.g À1 ) at 298 K, respectively. The results confirmed that the phenylene sulfide and oxidation product (sulfoxide and sulfone) were not involved in the coordination adsorption of Hg (II), and the adsorption mechanism of these resins for Hg(II) could been indicated in Fig.…”
Section: Adsorptive Performance Of the Hs-pps Ap-pps And Qa-pps Resinsmentioning
confidence: 95%
“…After agitating at 150 rpm, pH 5, and 30°C for 3 h, each set was filtered in order to measure the residual amounts of Pd 2+ cations and each co‐existing interfering metal cation. The following relationship was used to evaluate the imprinting effect on the selective extraction of Pd 2+ cations 41 D=()CiCfCf×VWwhere D , C i , and C f (mg/L) are the distribution coefficient and initial and final Pd 2+ concentrations, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Thus means that 'Synthesis and application of ion-imprinted resin based on modified melamine-thiourea for selective removal of Hg(II)' might not be correct. The same mistake has been mass duplicated by Monier et al in Carbohydrate Polymers, 2 the Chemical Engineering Journal, 3 Colloids and Surfaces B − Biointerfaces, 4 the International Journal of Biological Macromolecules, 5 -8 Journal of Applied Polymer Science, 9 Journal of Colloid and Interface Science, 10,11 Journal of Hazardous Materials, 12 -16 Journal of Molecular Recognition, 17 Polymer International 18 and Reactive and Functional Polymers. 19 In 1898, Lagergren first presented the first-order rate equation for the adsorption of oxalic acid and malonic acid onto charcoal.…”
mentioning
confidence: 98%
“…Recently, Monier et al published the paper entitled ‘Synthesis and application of ion‐imprinted resin based on modified melamine‐thiourea for selective removal of Hg(II)’ . In the section Adsorption kinetics, the authors noted: ‘For better evaluation of the extraction mechanism and investigation of the rate‐limiting step, the obtained kinetic results were treated by using both pseudo‐first‐order and pseudo‐second‐order kinetic models, which can be mathematically expressed as follows: 1normalqt=normalk1qenormalt+1normalqnormale tqt=1k2qe2+1qnormalet …”
mentioning
confidence: 99%